Multi-clinical index classifier combined with AI algorithm model to predict the prognosis of gallbladder cancer - Zhou, Yun; Chen, Siyu; Wu, Yuchen; Li, Lanqing; Lou, Qinqin; Chen, Yongyi; Xu, Songxiao (Frontiers in Oncology, 2023)
Objectives It is significant to develop effective prognostic strategies and techniques for improving the survival rate of gallbladder carcinoma (GBC). We aim to develop the prediction model from multi-clinical indicators combined artificial intelligence (AI) algorithm for the prognosis of GBC. Methods A total of 122 patients with GBC from January 2015 to December 2019 were collected in this study. Based on the analysis of correlation, relative risk, receiver operator characteristic curve, and importance by AI algorithm analysis between clinical factors and recurrence and survival, the two multi-index classifiers (MIC1 and MIC2) were obtained. The two classifiers combined eight AI algorithms to model the recurrence and survival. The two models with the highest area under the curve (AUC) were selected to test the performance of prognosis prediction in the testing dataset. Results The MIC1 has ten indicators, and the MIC2 has nine indicators. The combination of the MIC1 classifier and the “avNNet” model can predict recurrence with an AUC of 0.944. The MIC2 classifier and “glmet” model combination can predict survival with an AUC of 0.882. The Kaplan-Meier analysis shows that MIC1 and MIC2 indicators can effectively predict the median survival of DFS and OS, and there is no statistically significant difference in the prediction results of the indicators (MIC1: χ2 = 6.849, P = 0.653; MIC2: χ2 = 9.14, P = 0.519). Conclusions The MIC1 and MIC2 combined with avNNet and mda models have high sensitivity and specificity in predicting the prognosis of GBC.